How smart cities transform operations models: a new research agenda for operations management in the digital economy. Issue 6 (25th April 2016) - Li, Feng; Nucciarelli, Alberto; Roden, Sinead; Graham, Gary
Abstract: The notion of smart cities is growing in prominence in the digital economy. The integration of urban infrastructures with information and communication technologies enables the development of new operations models. Digitised infrastructures offer opportunities for public and private organisations to design and deliver more customer-centric products or services, particularly for those that require geographical proximity with consumers in the online to offline (O2O) context. A framework is developed and used to analyse three case examples. These cases illustrate the emergence of new operations models and, demonstrate how smart cities are redefining the characteristics of operations models around their scalability, analytical output and connectivity. We also explore the feasibility, vulnerability and acceptability of each new operation. This paper contributes to our understanding of how smart cities can potentially transform operational models, and sets out a research agenda for operations management in smart cities in the digital economy.